The song of Samsu Tabriz in Ronggasasmita’s Suluk Acih - Florida, Nancy (Wacana, Journal of the Humanities of Indonesia, 2021)
The article contributes an excerpt from the Karaton Surakarta poet Ronggasasmita’s Suluk Kutub (also known as Suluk Samsu Tabriz) along with an annotated translation of the text into English. Suluk Kutub is one of the metaphysical poems that belong to this Sufi poet’s Suluk Acih, a text that he compiled in Aceh in 1815. The poem is a Javanese rendition of the meeting of Jalaluddin Rumi (Jav. Mulana Amir Kaji Rum) with his beloved, Shamsuddin Tabrizi (Jav. Samsu Tabriz). The commentary forms a short meditation on, and guide to, the specific practices of translating Javanese poetry into English – performed in part in dialogue with Ronggasasmita.